Implementation Of the Holistic Integrative Early Child Development Program (PAUD-HI) in PAUD Units - Rizkha Hanifa; Sofia Hartati; Nurjannah (International Conferences on Early Childhood Education Proceedings, 2023)
According to the Presidential Regulation of the Republic Indonesia No. 60 of 2013 on Holistic Integrative Early Childhood Development (PAUD-HI), Holistic Integrative Early Childhood Education is an early childhood development effort carried out to meet children's diverse and interrelated essential needs simultaneously, systematically, and integratedly. Education, health, nutrition, care, care, protection, and welfare services are examples of holistic stimulation services. The goal of this study was to examine the teacher's understanding or point of view on the implementation of the Holistic Integrative PAUD service programme. This study is a descriptive qualitative study. This study requires data pertaining to the implementation of PAUD-HI services. The information was gathered through the use of interview data collection techniques, observation, and documentation. Data analysis techniques such as data reduction, data display, and conclusions and data verification were used in the data analysis. According to the findings of this study, the implementation of PAUD-HI services at Al-Mukhlisin Kindergarten of West Pasaman is going quite well and successfully, but the implementation still adheres to the standard of Presidential Regulation No. 60 of 2013. This is evident from data collection results, which include five inside services: education, health and nutrition, care, protection, and welfare. PAUD-HI that can be implemented as a whole and is integrated with human resources (teachers, parents, offices, school principals) is a critical success factor in PAUD-HI implementation.